Using SIMPKB to Improve PPG Students' Reading Comprehension during the COVID-19 Pandemic - Agus Supriyadi (Journal of Language Development and Linguistics, 2022)
This study aims to improve the reading ability of PPG students during the COVID-19 pandemic through the SIMPKB application which is connected to zoom and google meet. The research design used in this study was classroom action with four stages. While quantitative data came from students' reading texts before and after the test, qualitative data was collected through interviews and field notes from tutors. By compiling the data, categorizing the data, developing interpretations, and summarizing the findings, then the qualitative data is evaluated. Meanwhile, descriptive quantitative analysis was used to analyze quantitative data. The results showed that the students had mastered the skills to identify the main concepts, draw conclusions, and separate certain information from the text. In addition, they see SIMPKB as a supportive and flexible learning instrument. To ensure that SIMPKB is functioning properly, the PPG admin discusses how to improve the reading comprehension process of students through careful thinking, planning, and reflection. Statistical analysis of the students' pre and post test scores showed an increase from 66.9 to 86.9. The average post-test score for students is higher than the pre-test score. This study found that the ease of use of the SIMPKB program and the ability of tutors and lecturers to track student progress during the learning process helped students learn to read well.